Unravelling the transcriptional regulation of saccharomyces cerevisiae UGA genes: The dual role of transcription factor leu3 - Palavecino Ruiz, Marcos Daniel (2017)
Yeast cells can use γ-aminobutyric acid (GABA), a non-protein amino acid, as a nitrogen source that is mainly imported by the permease Uga4 and catabolized by the enzymes GABA transaminase and succinate-semialdehyde dehydrogenase, encoded by the UGA1 and UGA2 genes, respectively. The three UGA genes are inducible by GABA and subject to nitrogen catabolite repression. Hence, their regulation occurs through two mechanisms, one dependent on the inducer and the other on nitrogen source quality. The aim of this work was to better understand the molecular mechanisms of transcription factors acting on different regulatory elements present in UGA promoters, such as Uga3, Dal81, Leu3 and the GATA factors, and to establish the mechanism of the concerted action between them. We found that Gat1 plays an important role in the induction of UGA4 transcription by GABA and that Gzf3 has an effect in cells grown in a poor nitrogen source such as proline and that this effect is positive on UGA4 expression. We also found that Gln3 and Dal80 affect the interaction of Uga3 and Dal81 on UGA promoters. Moreover, our results indicated that the repressing activity of Leu3 on UGA4 and UGA1 occurs through Dal80 since we demonstrated that Leu3 facilitates Dal80 interaction with DNA. However, when the expression of GATA factors is null or negligible, Leu3 functions as an activator.